Swelling Properties and Environmental Responsiveness of Superabsorbent Composite Based on Starch-G-Poly Acrylic Acid/Organo-Zeolite. Issue 7 (2nd July 2016) - Zhang, Yan; Zhao, Lin; Chen, Yizhong
ABSTRACT: Star-g-poly (acrylic acid)/organo-zeolite 4A (S-g-PAA/OZ) superabsorbent composite was prepared by grafting partially neutralized acrylic acid onto starch in the presence of organo-zeolite 4A (OZ) as an inorganic component. The morphology was characterized with scanning electron microscopy (SEM). Energy dispersive spectrometer (EDS) analysis revealed the fine distribution of OZ in superabsorbent composite. The swelling kinetics of the composites were characterized by means of a Schott's second-order model. The effect of OZ concentration in the composite on the water absorbency and swelling behavior were tested. The swelling properties of the composites were evaluated in various environments; pH, salinity, temperature, urea solution, and solvent-water mixtures. The activation energy (ΔE) for water during the swelling process was also determined through Arrhenius plots. The results showed that the proper amount of OZ was beneficial for improvement of the water absorbent capacity and the initial swelling rate in distilled water. The optimum prepared composite with 10 wt % OZ, possessed the maximum water absorption (511g/g) in distilled water and (521 g/g) in 0.1 wt % urea solution. The results inferred that S-g-PAA/OZ superabsorbent composite can be exploited for agriculture and medical applications.